2016
DOI: 10.1021/acsami.6b03183
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Threshold Voltage in Organic Complementary Logic Circuits with an Electron-Trapping Polymer and Photoactive Gate Dielectric Layer

Abstract: We present controllable and reliable complementary organic transistor circuits on a PET substrate using a photoactive dielectric layer of 6-[4'-(N,N-diphenylamino)phenyl]-3-ethoxycarbonylcoumarin (DPA-CM) doped into poly(methyl methacrylate) (PMMA) and an electron-trapping layer of poly(perfluoroalkenyl vinyl ether) (Cytop). Cu was used for a source/drain electrode in both the p-channel and n-channel transistors. The threshold voltage of the transistors and the inverting voltage of the circuits were reversibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Furthermore, this method potentially improves the patterning resolution to be as small as a few hundreds of nanometers, which corresponds to the half-wavelength of UV radiation. Only a few studies have reported techniques that modulate the charge carriers via photoinduced surface modulation; [35,36] moreover, the efficacy of these techniques are hindered by hysteresis characteristics, high operational voltage, and complicated modulation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this method potentially improves the patterning resolution to be as small as a few hundreds of nanometers, which corresponds to the half-wavelength of UV radiation. Only a few studies have reported techniques that modulate the charge carriers via photoinduced surface modulation; [35,36] moreover, the efficacy of these techniques are hindered by hysteresis characteristics, high operational voltage, and complicated modulation processes.…”
Section: Introductionmentioning
confidence: 99%
“…A slight reduction in the drain current was observed, which might originate from the UV‐induced electron trapping effect of the CYTOP layer. [ 33–35 ] Meanwhile, such electron trapping effect played a positive role to the α‐6T photoresponsivity under UV irradiation. The strong UV absorption of the α‐6T layer and the electron trapping in the CYTOP layer induced the large threshold voltage shift of 5.5 V toward positive gate bias along with a noticeable increase in the I D in the α‐6T transistor.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers are now vouching for organic thin-film transistors (OTFTs) for fabricating imperceptible IoT devices with low costs and high material efficiencies because of their intrinsic flexibility and compatibility with the printing process. ,, One of the key fabrication techniques for tuning power consumption and operating speed of the devices is to control the turn-on voltage ( V on ), which is the voltage needed to reach a certain conductivity, or the threshold voltage ( V th ), which is the voltage at which a conductive channel is established between the source and drain electrodes, of both the p- and n-type transistors on a single substrate. The recently demonstrated silicon complementary metal-oxide semiconductor technology allows control of V on or V th via ion implantation in the channel . In the case of OTFTs, V on or V th is controlled by modulating the semiconductor–dielectric interfacial characteristics through self-assembled monolayers, oxygen plasma exposure, and material doping in organic semiconductors. However, these methods often require complex patterning processes, because of which tuning the power consumption and operating speed on a single substrate becomes a considerable technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum resolution of such a pattern is several hundred nanometers, which is approximately half of the incident light wavelength, and this maximum resolution is sufficiently high for fabricating organic integrated circuits. To date, a few studies have reportedly been conducted on interfacial photochemical reactions using photoreactive insulating polymers. , However, this seldom-reported polymer-based method is not suitable for fabricating flexible multimodal sensors because of their hysteresis characteristics and high driving voltages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation